The Language Function Used in Hospitality Advertisements during the Covid-19 Pandemic: The Language Function Used in Hospitality Advertisements during the Covid-19 Pandemic - Putri Aningsih, Ni Luh Sintya Melani; I Dewa Ayu Devi Maharani Santika; Ni Wayan Suastini (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
This research aimed to determine the use of language functions employed in hospitality advertisement during the covid-19 pandemic. The online flyer of Agata Hospitality served as the data source. The data was analysed using a descriptive qualitative method. Roman Jakobson theory (1960) was used to analyse the data. This research came to three results. First, the researcher discovered a total of 124 data, there were 62 data of referential function, 7 data of emotive function, 9 data of conative function, 38 data of phatic function, 7 data of poetic function and 1 data of metalingual function. Second, the most prevalent language function found is referential function and phatic function because mostly the content of the online flyers of Agata Hospitality contains the information of their product and services and aims to attract the attention and interest of the target audience. Lastly, the language functions used in online flyers have an important influence on attracting the attention, interest and curiosity of the target audience so that they make purchases or reservations during the pandemic.